A comparative study of wavelength-dependent photoinactivation in photosystem II of drought-tolerant photosynthetic organisms in Antarctica and the potential risks of photoinhibition in the habitat. - Kosugi, Makiko; Maruo, Fumino; Inoue, Takeshi; Kurosawa, Norio; Kawamata, Akinori; Koike, Hiroyuki; Kamei, Yasuhiro; Kudoh, Sakae; Imura, Satoshi (Annals of Botany, 2018)
journal article